The effectiveness of acupressure combination neiguan and zuzanli points to decrease emesis gravidarum in the first trimester of pregnancy - Siti Cholifah; Yanik Purwanti; Cholifah Cholifah; Dian Aprilia (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2022)
Background: Emesis gravidarum is the most common symptoms in pregnancy which about 50-90% causing a decrease in appetite and will affect changes in potassium, calcium and sodium electrolyte balance, thus will impact on changes in body metabolism. As much as 2% of pregnant women experienced excessive nausea and vomiting (hyperemesis gravidarum) which can harm the mother and fetus. The current management of emesis gravidarum still uses pharmacological therapy, but pharmacological methods are more expensive, and more potential to have side effects. Instead of pharmacological methods, non-pharmacological methods are cheap, simple, effective, and have no side effects. One of the non-pharmacological methods to treat nausea and vomiting is acupressure. Objectives: was to determine the effectiveness of the combination Neiguan point (PC6) & Zusanli point (ST 36) to decrease emesis Gravidarum in the first trimester of pregnancy in midwives independent practice Sidoarjo.Methods: This research used quasi-experimental with one group pretest-posttest design. The study population are pregnant women in the first trisemester who experienced emesis gravidarum, who met inclusion criteria and were willing to be studied and had no with consecutive sampling technique from February 2 to March 20, 2022 totaling 40 respondents. Measurement of emesis gravidarum using the Rhodes index instrument. Data analysis using Wilcoxon test with α 0.05.Results: The results showed that the score for emesis gravidarum before acupressure was Mean+SD 22.0+4.01, while the score for emesis gravidarum after acupressure was Mean+SD 13.0+3.14. The results of the Wilcoxon test showed P value = 0.001 < 0.05 so there was a significant difference in the emesis gravidarum score before and after acupressure was given. Conclusions: Acupressure at the Neiguan point (PC6) and Zusanli point (ST 36) is effective in reducing emesis gravidarum in first trimester of pregnant women. Health workers, especially midwives, can apply and teach acupressure to pregnant women to reduce nausea and vomiting complaints.